Kauzacijos samprata lingvistikoje - Rackevičienė, Sigita (Kalbotyra, 2000)
The aim of the article is to survey the conception of causation in various linguistic works. Linguists define causation as relation between two situations or events - one causing the occurrence of the other. A causative situation is often called a macrositaution which consists of two microsituations - causing and caused. Each microsituation contains at least two components - an actor and his action or state. Analysis of the surface structure of causation (causative constructions) reveals what formal means languages use for the expression of causation (constructions with a subordinate clause, prepositional phrases, causative verbs). This kind of research helps to find out what syntactic constructions are related semantically and which syntactic constructions can be compared with causative verbs. Special attention is given to constructions with causative verbs. The semantic analysis of constructions with causative verbs shows what types of causation can be expressed by verbs. That kind of research can help to improve semantic classification of verbs.